Synthesis of N2, N6-bis(5-methylthiazol-2-yl)pyridine-2,6-dicarboxamide fluoroscent sensor for detection of Cu2+ and Ni2+ Ions - Kumar, Anuroop; Singh, Netrapal; Kumar, Mordhwaj; Agarwal, Uma (Drug Research, 2021)
This article reports an amide based Chemosensor used for selective detection of divalent Cu+2 and Ni+2 ions via Fluorescence turn off. The selective sensing ability of Chemosensor was investigated in presence of different metal ions Mg2+, Ag+, Fe2+, K+, Cu2+, Ni2+, Hg2+, Pb2+, Mn2+, Pd2+, Cd2+ and Mn3+ as competitive ions. The receptor i. e. Chemosensor formed complexes with metal ions in 1:1 stoichiometric ratio. The detection limit and binding constant calculated as 1.92×10–4 and 1.4×10–4 M and 2.16×103 M−1 and 3.09×103 M−1 for Cu2+ and Ni2+ions respectively. The complexes were characterized by UV/visible, FT-IR, 13C NMR and 1H NMR spectroscopy. Further the structure and Crystallinity were calculated by P-XRD spectral analysis. The crystallinity found to be 65.27 and 67.87% respectively
Keywords: fluorescence quenching; chemosensor; Cu2+ and Ni2+ ions detection; binding constant chemistry; screening; toxicology